Wheat Gluten-Laminated Paperboard with Improved Moisture Barrier Properties: A New Concept Using a Plasticizer (Glycerol) Containing a Hydrophobic Component (Oleic Acid) - Sung-Woo Cho; Thomas O. J. Blomfeldt; Helena Halonen; Mikael Gällstedt; Mikael S. Hedenqvist (International Journal of Polymer Science)
This paper presents a novel approach to reduce the water vapor transmission rate (WVTR) and water absorbance of wheat gluten/paperboard laminates by introducing a hydrophobic component (oleic acid (OA)) into the hydrophilic plasticizer (glycerol). Whereas the paperboard showed immeasurably high WVTR, the laminate with gluten/glycerol yielded finite values. More importantly, by incorporating 75 wt.% OA into the plasticizer, the WVTR and water absorbance were reduced by, respectively, a factor of three and 1.5–2. Of particular interest was that the mechanical properties were not changing dramatically between 0 and 50 wt.% OA. The results showed clear benefits of combining a gluten film with paperboard. Whereas the paperboard provided toughness, the WG layer contributed with improved moisture barrier properties. In addition, WVTR indicated that the paperboard reduced the swelling of the outer gluten/glycerol layer in moist conditions; a free standing gluten/glycerol film would yield infinite, rather than finite, WVTR values.